The effect of enhanced microwave system (EMS) on the recycling of elastic polyurethane foam - Ergan, Basak Temur (Gazi Univ, Fac Engineering Architecture, 2020)
Tin (II) 2-ethylhexanoate (Stannous octoate) was used as a catalyst in this study where flexible polyurethane (PU) foam was examined by glycolysis (recycle) with diethylene glycol (DEG) in a simultaneous cooled microwave (MW) system. Then the reaction variables (PU / DEG ratio and % stannous octoate by weight), process variables (temperature (T), time (t), MW power (P)) and their working ranges were determined. PU / DEG ratio and temperature (T) variables were fixed by reading the related literature and considering working conditions in the established MW system. The effects of three other variables (P, t, % Stannous octoate by weight) on glycolysis yield (polyol yield) and MW energy consumption were investigated. The optimum process conditions for the maximum yield were determined by spending minimum energy in operation. Then, the experiment on the optimum condition was repeated by the conventional method (CH) on the same conditions, and the effect of MW was examined comparatively. Accordingly, it was found that the yield of polyol in MW-assisted glycolysis during the same period was 46.6% higher than CH counterparts. Furthermore, energy saving was accomplished by 78% and an increase of polyol production rate by 46.7 % in MW method.
Geliştirilmiş mikrodalga sisteminin elastik poliüretan köpüğünün geri dönüşümüne etkisi
Keywords: Enhanced microwave system simultaneous cooling; polyurethane; glycolysis; polyol